PENGARUH LATIHAN CORE STABILITY EXERCISE TERHADAP PENINGKATAN KESEIMBANGAN TUBUH PADA PEMAIN PS.UNDIKMAMATARAM TAHUN 2019 - Susi Yundarwati; Soemardiawan Soemardiawan (Prosiding Seminar Nasional Lembaga Penelitian Dan Pendidikan (LPP) Mandala)
The focus of the problem in this study was during the training and competition of the PS players. UNDIKMA Mataram is lacking in passing, dribbling, control, shooting, because it is not good in exercising body balance in doing a body charge that easily falls. Therefore there are exercises Core stability exercise exercises to increase body balance in PS players. UNDIKMA Mataram in 2019. The formula in the research problem is